50 student volunteers experience crisis management - Nor Salwana, Mohammad Idris (2020)
Kuantan, 14 May 2020 - A total of 50 students from Universiti Malaysia Pahang (UMP) will undoubtedly remember their experience in volunteering for managing the welfare and safety and the operation of sending back home of the students who were stranded in the campus for more than 40 days following the Movement Control Order (MCO).